Managing the negative impact of workforce diversity: The important roles of inclusive HRM and employee learning-oriented behaviors - Liu, Jiakun; Zhu, Yufeng; Wang, Huatian (Frontiers in Psychology, 2023)
The workforce has become more diverse than it used to be. Although organizations actively capitalize on workforce diversity to enhance team innovation and organizational performance, it is found that workforce diversity also has potential risks, among which interpersonal conflict is the most salient one. However, we still know relatively less about why workforce diversity may link to higher interpersonal conflict and, more importantly, how to mitigate the negative impact of workforce diversity. Based on the workplace diversity theories (e.g., the categorization-elaboration model), this study examined how workforce diversity was positively related to interpersonal conflict through impacting one’s affective states, and to what extent this indirect effect can be weakened by organization-initiated practices (i.e., the inclusive human resources management (HRM) practices) and employee-initiated behaviors (i.e., employee learning-oriented behaviors). Using two-wave surveys from 203 employees from various organizations in China, we confirmed our hypotheses. Our results showed that perceived workforce diversity was positively related to interpersonal conflict through increasing negative affect (after we controlled for the objective diversity level calculated by the Blau index), and this indirect effect was weakened when the levels of inclusive HRM practices and employee learning-oriented behaviors were high. Our study suggests that it is important for organizations to be aware of the detrimental impact of workforce diversity. In addition, it is essential to use both the top-down (e.g., inclusive HRM practices) and bottom-up (e.g., employee learning-oriented behaviors) approaches to managing the challenges presented by diversity so as to unlock more potential of diversity in the workplace.